Barriers to and facilitators of smoking cessation in pregnancy and following childbirth: literature review and qualitative study - Linda Bauld; Hilary Graham; Lesley Sinclair; Kate Flemming; Felix Naughton; Allison Ford; Jennifer McKell; Dorothy McCaughan; Sarah Hopewell; Kathryn Angus; Douglas Eadie; David Tappin (Health Technology Assessment, 2017)
Background: Although many women stop smoking in pregnancy, others continue, causing harm to maternal and child health. Smoking behaviour is influenced by many factors, including the role of women’s significant others (SOs) and support from health-care professionals (HPs). Objectives: To enhance understanding of the barriers to, and facilitators of, smoking cessation and the feasibility and acceptability of interventions to reach and support pregnant women to stop smoking. Design: Four parts: (1) a description of interventions in the UK for smoking cessation in pregnancy; (2) three systematic reviews (syntheses) of qualitative research of women’s, SOs’ and HPs’ views of smoking in pregnancy using meta-ethnography (interpretative approach for combining findings); (3) semistructured interviews with pregnant women, SOs and HPs, guided by the social–ecological framework (conceptualises behaviour as an outcome of individuals’ interactions with environment); and (4) identification of new/improved interventions for future testing. Setting: Studies in reviews conducted in high-income countries. Qualitative research was conducted from October 2013 to December 2014 in two mixed urban/rural study sites: area A (Scotland) and area B (England). Participants: Thirty-eight studies (1100 pregnant women) in 42 papers, nine studies (150 partners) in 14 papers and eight studies described in nine papers (190 HPs) included in reviews. Forty-one interviews with pregnant women, 32 interviews with pregnant women’s SOs and 28 individual/group interviews with 48 HPs were conducted. Main outcome measures: The perceived barriers to, and facilitators of, smoking cessation in pregnancy and the identification of potential new/modified interventions. Results: Syntheses identified smoking-related perceptions and experiences for pregnant women and SOs that were fluid and context dependent with the capacity to help or hinder smoking cessation. Themes were analysed in accordance with the social–ecological framework levels. From the analysis of the interviews, the themes that were central to cessation in pregnancy at an individual level, and that reflected the findings from the reviews, were perception of risk to baby, self-efficacy, influence of close relationships and smoking as a way of coping with stress. Overall, pregnant smokers were faced with more barriers than facilitators. At an interpersonal level, partners’ emotional and practical support, willingness to change smoking behaviour and role of smoking within relationships were important. Across the review and interviews of HPs, education to enhance knowledge and confidence in delivering information about smoking in pregnancy and the centrality of the client relationship, protection of which could be a factor in downplaying risks, were important. HPs acknowledged that they could best assist by providing support and understanding, and access to effective interventions, including an opt-out referral pathway to Stop Smoking Services, routine carbon monoxide screening, behavioural support and access to pharmacotherapy. Additional themes at community, organisational and societal levels were also identified. Limitations: Limitations include a design grounded in qualitative studies, difficulties recruiting SOs, and local service configurations and recruitment processes that potentially skewed the sample. Conclusions: Perceptions and experiences of barriers to and facilitators of smoking cessation in pregnancy are fluid and context dependent. Effective interventions for smoking cessation in pregnancy should take account of the interplay between the individual, interpersonal and environmental aspects of women’s lives. Future work: Research focus: removing barriers to support, improving HPs’ capacity to offer accurate advice, and exploration of weight concerns and relapse prevention. Interventions focus: financial incentives, self-help and social network interventions. Study registration: This study is registered as PROSPERO CRD42013004170. Funding: The National Institute for Health Research Health Technology Assessment programme.